Balanced scorecard no planejamento estratégico da diretoria de educação a distância da Universidade Federal de Lavras - Pires, Tatiana Cubiaki (2018)
Globalization has directly affected the organizations and people, once it is no different when it is about to public institutions, especially higher education institutions (HEIs). The HEIs have been intensifying and pushing efforts to this phenomenon to reach the expected result. In this context, the elaboration of an adequate strategic plan to the characteristics of the organization is essential. The objective in this study was to develop a proposal of strategic planning using the Balanced Scorecard, for the Distance Education Direction ( DIRED) of the Federal University of Lavras - UFLA), a public institution located in Minas Gerais, Brazil. The study is justified, since it is necessary to understand these organizations, private or public, monitoring their processes and results. These organizations should strive for to define the ir mission, vision, values and know their weak and strengths, weaknesses, opportunities and threats analysis (SWOT), contributing for the achievement of their goals and to maximize their results. This study had as main motivation to obtain information that promote the elaboration of a strategic planning, by using Balanced Scorecard BSC, allowing to visualize the organization from several perspectives at the same time. For the work development, the BSC model was created for the public sector based on the model created by Martins (2005). The methodology used to conduct the study was the case study developed in DIRED/UFLA. Therefore, we used documentary research, participant observation and workshops, in order to gather subsidies that would provide the elaborat ion of the model. The results analysis provided the identification of four perspectives to be used in the proposed BSC: 1. Budget perspective; 2. Perspective of people and technology; 3. Perspective of internal processes and 4. Perspective of institutional results. From the definition of these perspectives, the strategic map to be used by the board of directors was presented. Lastly, the research showed up that BSC performed itself as a capable management tool to support DIRED to organize its activities and to evaluate its results.